Adolescents' perceptions of standardised cigarette packaging design and brand variant name post-implementation: a focus group study in Scotland - Danielle Mitchell; Crawford Moodie; Nathan Critchlow; Linda Bauld (BMC, 2019)
Abstract Background The United Kingdom (UK) fully-implemented standardised packaging for cigarettes and rolling tobacco on 20th May 2017. We explore adolescent's awareness of, and responses to, standardised cigarette packaging in the UK after it became mandatory. Methods Eight focus groups were conducted in schools in Scotland with 16-17 year-olds (n = 41), between November 2017 and November 2018, to explore awareness of, and responses to, standardised cigarette packaging. Unlike in Australia, where only straight-edged flip-top cigarette packs are permitted, in the UK standardised cigarette packs can have slim designs, and different edge types (straight, rounded or bevelled) and opening styles (flip-top or shoulder box). We explored how each of these pack formats was perceived. We also explored to what extent brand variant name differentiated cigarettes sold in standardised packaging. Results Most participants were aware of standardised packaging without being shown pack stimuli. Standardised packs were considered embarrassing and off-putting, and the health warnings salient. Among the standardised packs shown, there was a preference for the slimmer pack, viewed as more discrete and the cigarettes potentially less harmful, and the shoulder box, considered cool and different. Participants were interested in some brand variant names on standardised packs (e.g. Legendary Black), particularly those they considered to imply coolness and sophistication. Conclusion Adolescents consider standardised cigarette packs in the UK unappealing, and the warnings salient, two core aims of this measure. However, positive reactions to some of the standardised packs (slimmer pack, shoulder box), and variant names used, has implications for countries developing standardised packaging regulations.